2019
DOI: 10.3390/vaccines7030110
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Immune Response to Rabies Vaccination: A Systematic Review

Abstract: The effectiveness of rabies vaccines is conventionally determined by serological testing. In addition to this assessment of humoral immunity, cellular immunity could help assess effectiveness and protection through a broad range of parameters. Therefore, this study aimed to systematically review all literature on the kinetics and composition of the cellular immune response to rabies vaccination in humans. A total of 1360 studies were identified in an extensive literature search. Twenty studies were selected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 28 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…Following vaccination against influenza or TBE, we observed a robust expansion of DN B cells between day-4 and day-14, maximal at day-7. The increased fraction of DN B cells was accompanied by an expansion of plasmablasts at day-7 which is in line with the literature (50,51). Although detailed information is not available, a recent study also described the induction of DN B cells after vaccination with influenza virus (52).…”
Section: Discussionsupporting
confidence: 92%
“…Following vaccination against influenza or TBE, we observed a robust expansion of DN B cells between day-4 and day-14, maximal at day-7. The increased fraction of DN B cells was accompanied by an expansion of plasmablasts at day-7 which is in line with the literature (50,51). Although detailed information is not available, a recent study also described the induction of DN B cells after vaccination with influenza virus (52).…”
Section: Discussionsupporting
confidence: 92%
“…Based on current data, the VNAs produced following rabies vaccines will likely not be protective against LBV infection. However, it has been suggested that several other components of the immune response (that is currently not completely understood or characterized) may play an important role in protection in addition to VNAs [ 69 ]. No human LBV cases have been reported to date; however, there is a potential spillover risk, since several human exposures have been associated with animals infected with LBV.…”
Section: Preventionmentioning
confidence: 99%
“…Their efficacy has been demonstrated in a variety of wild carnivore reservoir species [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Conventionally, the effectiveness of rabies vaccines in wildlife target species is determined by serological testing [ 24 ], e.g., the detection of rabies virus neutralizing (VNA) or binding antibodies as a surrogate for humoral immune response and hence, adequate B-cell response [ 25 ]. Apart from that, independent of the humoral response, survival after the challenge is another criteria for licensing [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%